Educators in Islam: A Study of Their Status, Roles, Duties, and Challenges from the Perspective of Islamic Education - Lalu Yusri Bahtiar; Syarifuddin Ondeng; Munawir Kamaluddin (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Education in Islam is not merely aimed at transferring knowledge, but also at shaping the character, morals, and spirituality of learners toward becoming a perfect human being (insan kamil). One of the key components that determines the success of such education is the educator. This study aims to examine the definition, position, duties and roles, characteristics, as well as challenges faced by educators from an Islamic perspective. This research employs a qualitative method using a library research approach, where data are collected through the review and analysis of literature such as books and scientific journals, as well as primary sources including the Quran and Hadith relevant to the theme of educators in Islam. The data are analyzed using content analysis through a descriptive-qualitative technique. The findings indicate that the term "educator" in Islam carries a broad meaning, reflected in various designations such as murabbi, mu'allim, muaddib, mudarris, mursyid, and muzakki, each representing a distinct dimension of their role. The position of an educator in Islam is highly honorable, even comparable to that of the Prophets, since the knowledge they teach ultimately originates from Allah SWT. The duties and roles of an educator cover instructional, educational, and managerial functions, while their ideal characteristics include faith, knowledge, sincerity, fairness, and consistency in practicing what they teach. Furthermore, educators in Islam today face three main challenges: the advancement of science and technology, democratization, and moral decline. This study recommends strengthening both the spiritual and professional competencies of educators so that they can respond to contemporary challenges without abandoning Islamic values.